2013
DOI: 10.4103/0971-4065.109410
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria in Nigerian children with sickle cell anemia

Abstract: Urinary tract infections (UTI) in children with sickle cell anemia (SCA) may result in long term renal dysfunction. The prevalence, potential risk factors, and clinical significance of asymptomatic bacteriuria (ASB) were investigated in 196 Nigerian children with SCA in stable state. These children had clinical evaluation and assessment of their mid-stream urine (MSU) for pyuria, culture, and sensitivity tests; urinalysis for proteinuria, and estimated glomerular filtration rate (eGFR), hematocrit, serum creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…Asymptomatic bacteriuria did not appear to be persistent in the 11 cases who were initially diagnosed in 2004, with only two (18%) patients having documented ASB in 2010. This was similar to the report of Adegoke where only 2 of 13 patients had persistent ASB after six months of follow-up (14). The lack of persistence of ASB perhaps suggests the transitory nature of the diagnosis and further underscores the lack of guidelines supporting screening or implementation of antibiotic therapy in patients with SCD and ASB.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Asymptomatic bacteriuria did not appear to be persistent in the 11 cases who were initially diagnosed in 2004, with only two (18%) patients having documented ASB in 2010. This was similar to the report of Adegoke where only 2 of 13 patients had persistent ASB after six months of follow-up (14). The lack of persistence of ASB perhaps suggests the transitory nature of the diagnosis and further underscores the lack of guidelines supporting screening or implementation of antibiotic therapy in patients with SCD and ASB.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of ASB in SCD is reported to range from 4% to 6.6% (3,10,13,14). This rate does not appear to differ significantly from the reported prevalence rate of 5% in healthy premenopausal women without SCD (15).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Sterile pyuria has also been noted in other polyarthritis syndromes in children including: reactive arthritis, juvenile idiopathic arthritis, polyarteritis nodosa and Henoch Schonlein purpura. 39 Adegoke and Adegun 40 in a study of asymptomatic bacteriuria in children with sickle cell anemia found a prevalence of 18.2% of sterile pyuria. This was thought to be due to repeated infarction and papillary necrosis.…”
Section: Non-infectious Causes Of Sterile Pyuriamentioning
confidence: 99%